Campylobacter infection presenting as pseudo-appendicitis in children: identifying predictors for early diagnosis - Schnapper, Michael; Kahan, Yaara; Klivitsky, Amir; Guri, Alex; Shatzman Steuerman, Rachel; Heled Akiva, Maya; Tasher, Diana (Frontiers in Pediatrics, 2025)
AimsTo characterize Campylobacter enteritis presenting as pseudo-appendicitis and identify distinguishing predicting factors.MethodsThis retrospective multicentre study included all children <18 years with confirmed Campylobacter infection, hospitalized from 2014 to 2023 for presumed appendicitis (pseudo-appendicitis group). Each case was matched with 2 controls with confirmed appendicitis. Multivariable logistic regression analysis was conducted to determine the potential predictors for pseudo-appendicitis.ResultsFifty-five cases of pseudo-appendicitis were compared with 110 cases of appendicitis. The rate of peritoneal signs was similar between the two groups (78.2% vs. 75.5%, P = 0.07). Computed-tomography (CT) scans were performed nearly twice as often in the pseudo-appendicitis group (38% vs. 20%, P = 0.01). Broad-spectrum antibiotics were administered to 19 (34.5%) of patients with pseudo-appendicitis and none had surgery. Independent predictors of pseudo-appendicitis included: history of fever (OR: 17.2, 95% CI: 4.7–62.9, P < 0.01), WBC <12,000/μl (OR: 9.6, 95% CI: 2.9–31, P < 0.01), sonographic signs of enlarged mesenteric lymphadenopathy and/or ileocolitis (OR:5.8, 95% CI:1.8–18.6, P = 0.03), no sonographic sign of appendicitis (OR: −5.8, 95% CI: 1.3–25, P = 0.02), diarrhea (OR: 3.7, 95% CI:1.2–11.3, P = 0.02), and age >14 years (OR:3.3, 95% CI:0.91–12, P = 0.06).ConclusionThe diagnostic challenge of Campylobacter pseudo-appendicitis notably led to high rates of CT imaging and unnecessary broad-spectrum antibiotic administration. We identified predictors that may prompt clinicians to consider Campylobacter enteritis in selected cases of suspected appendicitis, potentially encouraging early molecular diagnosis and improving patient care.